1999
DOI: 10.1073/pnas.96.17.9469
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked protein crystals for vaccine delivery

Abstract: The progress toward subunit vaccines has been limited by their poor immunogenicity and limited stability. To enhance the immune response, subunit vaccines universally require improved adjuvants and delivery vehicles. In the present paper, we propose the use of cross-linked protein crystals (CLPCs) as antigens. We compare the immunogenicity of CLPCs of human serum albumin with that of soluble protein and conclude that there are marked differences in the immune response to the different forms of human serum albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…The use of seeds for directed, tissue-specific subunit vaccine production offers several potential advantages. First, particulate antigens are known to induce a stronger immune response than soluble proteins, regardless of immunization route [39,40]. Data from studies with recombinant subunit vaccines delivered in plant seeds that were either whole, crudely ground, or otherwise minimally processed have confirmed that this general principle applies equally to plant-derived vaccines [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 93%
“…The use of seeds for directed, tissue-specific subunit vaccine production offers several potential advantages. First, particulate antigens are known to induce a stronger immune response than soluble proteins, regardless of immunization route [39,40]. Data from studies with recombinant subunit vaccines delivered in plant seeds that were either whole, crudely ground, or otherwise minimally processed have confirmed that this general principle applies equally to plant-derived vaccines [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the NSOM/QD-based nanoscale proteomic analysis would not overestimate V-PA immunogen loading, but allows us to conclude that high-density V-PA immunogen nanoclusters were loaded on the surface of GEM vaccine particle. It is also worth to point out that high-density of immunogen nanoclusters loaded on particle surface may be one of the important immune features of a highly immunogenic particle vaccine as a large amount of immunogen could be readily exposed to the immune system for eliciting robust immune responses [33, 34]. …”
Section: Resultsmentioning
confidence: 99%
“…Burroughs et al 112 reported the immunogenicity of protein crystals and Clair et al 113 concluded that the immunogenicity of cross-linked human serum albumin crystals was better than that of soluble proteins. Burroughs et al 112 reported the immunogenicity of protein crystals and Clair et al 113 concluded that the immunogenicity of cross-linked human serum albumin crystals was better than that of soluble proteins.…”
Section: Oral Deliverymentioning
confidence: 99%